Diagnostic performance of cerebroplacental and umbilicocerebral ratio in appropriate for gestational age and late growth restricted fetuses attempting vaginal delivery: a multicenter, retrospective study. (12th December 2022) - Villalain, Cecilia; Galindo, Alberto; Di Mascio, Daniele; Buca, Danilo; Morales-Rosello, Jose; Loscalzo, Gabriela; Giulia Sileo, Filomena; Finarelli, Alessandra; Bertucci, Emma; Facchinetti, Fabio; Rizzo, Giuseppe; Brunelli, Roberto; et al.
Abstract: Background: Cerebroplacental Doppler studies have been advocated to predict the risk of adverse perinatal outcome (APO) irrespective of fetal weight. Objective: To report the diagnostic performance of cerebroplacental (CPR) and umbilicocerebral (UCR) ratios in predicting APO in appropriate for gestational age (AGA) fetuses and in those affected by late fetal growth restriction (FGR) attempting vaginal delivery. Study design: Multicenter, retrospective, nested case-control study between 1 January 2017 and January 2020 involving five referral centers in Italy and Spain. Singleton gestations with a scan between 36 and 40 weeks and within two weeks of attempting vaginal delivery were included. Fetal arterial Doppler and biometry were collected. The AGA group was defined as fetuses with an estimated fetal weight and abdominal circumference >10th and <90th percentile, while the late FGR group was defined by Delphi consensus criteria. The primary outcome was the prediction of a composite of perinatal adverse outcomes including either intrauterine death, Apgar score at 5 min <7, abnormal acid-base status (umbilical artery pH < 7.1 or base excess of more than −11) and neonatal intensive care unit (NICU) admission. Area under the curve (AUC) analysis was performed. Results: 646 pregnancies (317 in the AGA group and 329 in the late FGR group) were included. APO were present in 12.6% AGA and 24.3% late FGR pregnancies, with an odds ratio of 2.22 (95% CI 1.46–3.37). The performance of CPR and UCR for predicting APO was poor in both AGA [AUC: 0.44 (0.39–0.51)] and late FGR fetuses [AUC: 0.56 (0.49–0.61)]. Conclusions: CPR and UCR on their own are poor prognostic predictors of APO irrespective of fetal weight.